The karst landscapes of Beni Mellal Atlas (central Morocco): identification for promoting geoconservation and tourism - Barka, Abdellah Ait; Rais, Jamila; Barakat, Ahmed; Louz, Elhassan; Nadem, Samir (Quaestiones Geographicae, 2022)
The Atlas of Beni Mellal is located in the Moroccan central High Atlas, characterized by an important geo-di-versity that attracts tourists every year. However, the number of visitors remains limited due to the lack of the promo-tion means, enhancement and mediation of this heritage. The obtained data indicate that the studied area preserves a great number of karst geosites, such as ruiniform landscapes, caves, poljes, sinkholes, Karren, shaft cave and many remarkable reliefs such as canyons and cliffs. This work concerns the inventory, the quantitative evaluation and the en-hancement of the remarkable geomorphosites. The results reveal the presence of 21 sites, including six karst forms; five ruiniform landscapes and one karren form, one enviable panoramic viewpoint and five karst springs, four caves, two travertines, two waterfalls, and one structural relief geosite; canyon, and one tepee structures. However, these sites are not protected against all types of degradation, because the general public does not recognize them. These karst forms are very vulnerable, they cannot reproduce quickly, and their deterioration leads to their permanent disappearance. That is why this heritage must be the object of a particular attention of the whole community. The valorisation of these geomorphologic assets is the proposal of a number of circuits and geotourist routes from the perspective of local and integrated development.